Pengaruh Promosi Jabatan dan Gaji Terhadap Kinerja Pegawai - Jeri Aldy; Achmad Efendi; Jubaidi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Job promotion and salary are a little sensitive in education, especially for employees. The lack of transparency in job promotions the provision of relatively low wages and the lack of details about salaries have an impact on employees. This study aims to analyze the effect of job promotion and salary on employee performance at SD Muhammadiyah 1 Samarinda. The study sample amounted to 67 employees at SD Muhammadiyah 1 Samarinda The data analysis technique used was multiple linear analysis. The results of this analysis show: (1) Job promotion has a partial effect with a significant value. 0.000 <0.05 on employee performance. (2) Salary has a partial effect with a sig value. 0.004 <0.05 on employee performance. (3) Job promotion and salary have a significant effect simultaneously with a significance value of (0.000) <0.005 on employee performance.